PENGEMBANGAN ALAT DETEKSI KANDUNGAN NUTRISI TANAH DENGAN SENSOR NPK DAN METODE HARDWARE PROGRAMMING - Denih, Asep; Ismangil, Agus; Kurnia, Ema (Universitas Teknokrat Indonesia, 2024)
In the agricultural sector, soil nutrient content has a very important role. Many farmers rely on limited information when selecting soil for cultivation, which often leads to crop failure and losses due to mismanagement of the soil. To overcome this problem, this study created a soil nutrient detection system that can help farmers classify the soil nutrients needed. This research uses the Soil NPK Sensor, where the determination of nutrient content is carried out through three main parameters, namely the value of N, P, and K. The data obtained from these sensors is then processed by the Arduino Wemos Esp32 microcontroller using the Hardware Programming Method. This research aims to develop a soil nutrient content detection tool that includes measurements of Moisture, pH, Nitrogen, Phosphorus, and Potassium. The tool uses NPK sensors embedded in the ground to collect data, which is then sent to Blynk's pre-programmed platform. The test results showed the performance of the tool with average levels up and down for Nitrogen of 8.2mg/Kg, Phosphorus 3.2mg/Kg, and Potassium 5.8mg/Kg. Overall, the average NPK content in the soil was Nitrogen 75mg/Kg, Phosphorus 64.3333mg/Kg, and Potassium 67.1667mg/Kg. This data can be accessed and monitored by farmers or users through the Blynk application on smartphones or laptops. The main focus of the study is to evaluate the performance of detection tools and provide relevant information for farmers in managing their land more efficiently.